The sociopolitical effects of ideological change: The Buddhist conversion of Maharashtrian untouchables - Gokhale, Jayashree B. (The journal of Asian studies, 1986)
On 14 October 1956, thousands of Maharashtrian untouchables, led by Dr. B. R. Ambedkar, renounced their ancestral faith and converted en masse to Buddhism. The essay treats the origins of that conversion, the institutions that were established as a result of it, the ideology that was formulated around it and the processes of social change that followed it. Mahars as the most numerous of the untouchable communities of Maharashtra. Institutions associated with the educational and cultural aspects of the Mahar-Buddhist movement. (DÜI-Sen)